2021
DOI: 10.3390/jcm10163752
|View full text |Cite
|
Sign up to set email alerts
|

JAK Inhibition with Ruxolitinib in Patients with COVID-19 and Severe Pneumonia: Multicenter Clinical Experience from a Compassionate Use Program in Italy

Abstract: Jak inhibitors are potent anti-inflammatory drugs that have the potential to dampen the hyperactive inflammatory response associated with severe COVID-19. We reviewed the clinical outcomes of 218 patients with COVID-19 hospitalized for severe pneumonia and treated with ruxolitinib through a compassionate use program. Data on the duration of treatment; outcomes at 4, 7, 14, and 28 days; oxygen support requirements; clinical status; and laboratory parameters were retrospectively collected. Overall, according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Ruxo has been repurposed for the treatment of SARS-CoV-2 infection in different clinical settings inside and outside of clinical trials, but the clinical significance of this drug in COVID-19 pneumonia and ARDS remains to be firmly established ( 18 , 20 , 21 , 32 , 56 , 59 62 ). The work presented here adds to previous work on the mechanisms of action of Ruxo in hyperinflammation and respiratory distress ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ruxo has been repurposed for the treatment of SARS-CoV-2 infection in different clinical settings inside and outside of clinical trials, but the clinical significance of this drug in COVID-19 pneumonia and ARDS remains to be firmly established ( 18 , 20 , 21 , 32 , 56 , 59 62 ). The work presented here adds to previous work on the mechanisms of action of Ruxo in hyperinflammation and respiratory distress ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ruxolitinib, an inhibitor of JAK1 and JAK2 is an orally administered drug approved for the treatment of myelofibrosis and polycythemia vera in Europe ( 122 ). Several newly developed agents have been tested to determine their efficacy in treating COVID-19, including Baricitinib ( 123 ), Clazakizumab, Siluximab and Anakinra ( 124 ).…”
Section: Severe Atypical Respiratory Syndrome-coronavirus-2 (Sars-cov...mentioning
confidence: 99%
“…Approximately 87.2% of the patients were alive at the end of the observation period. There were no unexpected safety results, and patients reported minor side effects ( 175 ). In a study by Koschmieder et al patients with COVID-19 were shown to be at risk for severe disease, especially those with comorbidities.…”
Section: Jak Inhibitors As Therapeutic Agents Against Covid-19mentioning
confidence: 99%